2013
DOI: 10.2337/db12-0828
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Local Production of Proresolving Lipid Mediators in Obesity and 17-HDHA as a Potential Treatment for Obesity-Associated Inflammation

Abstract: Obesity-induced chronic low-grade inflammation originates from adipose tissue and is crucial for obesity-driven metabolic deterioration, including insulin resistance and type 2 diabetes. Chronic inflammation may be a consequence of a failure to actively resolve inflammation and could result from a lack of local specialized proresolving lipid mediators (SPMs), such as resolvins and protectins, which derive from the n-3 polyunsaturated fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). We as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
162
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(187 citation statements)
references
References 55 publications
(67 reference statements)
16
162
1
3
Order By: Relevance
“…The -3 fatty acids are further metabolized into resolvins, which are involved in resolution of inflammation (169), a persistent process in diabetes. Hence resolvin supplementation or targeting pathways of resolvin synthesis could help alleviate systemic and local adipose tissue inflammation (242) and represent an effective approach against diabetes. Similar opportunities may also arise from exploring the products of gut microbiota…”
Section: Bioactive Lipids and Regulation Of Inflammationmentioning
confidence: 99%
“…The -3 fatty acids are further metabolized into resolvins, which are involved in resolution of inflammation (169), a persistent process in diabetes. Hence resolvin supplementation or targeting pathways of resolvin synthesis could help alleviate systemic and local adipose tissue inflammation (242) and represent an effective approach against diabetes. Similar opportunities may also arise from exploring the products of gut microbiota…”
Section: Bioactive Lipids and Regulation Of Inflammationmentioning
confidence: 99%
“…Similarly, intraperitoneal injection (nanogram amounts) of RvE1 to obese ob/ob mice confers significant insulinsensitizing effects by mechanisms related to the AMPKadiponectin axis and the induction of GLUT-4 and IRS-1 expression (Gonzalez-Periz et al, 2009). In addition, 17S-HDHA treatment (intraperitoneal injection of nanogram doses) reduces adipose tissue expression of inflammatory cytokines (MCP-1, TNFa, IL-6 and osteopontin), increases adiponectin expression and improves glucose tolerance in parallel with insulin sensitivity in obese/diabetic db/db mice (Neuhofer et al, 2013). Similar beneficial actions in adipose tissue physiology have been described for LXA 4 in an experimental model of adipose tissue inflammation associated with aging (Borgeson et al, 2012).…”
Section: Biological Actions Of Omega-3-derived Lipid Mediators In Watmentioning
confidence: 53%
“…In the setting of obesity, prevailing data support an unbalanced formation of these omega-3-derived lipid mediators in obese WAT. Indeed, a deficit in tissue SPM levels (RvD1, PD1 and 17-HDHA) has been characterized in inflamed visceral and subcutaneous fat compartments from obese ob/ob and obese/diabetic db/db mice (Gonzalez-Periz et al, 2009;Claria et al, 2012;Neuhofer et al, 2013). In humans, a deficit in PD1 and its precursor 17S-HDHA has been reported in subcutaneous fat from patients with peripheral vascular disease in whom the inflammatory status in adipose tissue is remarkably exacerbated compared with healthy subcutaneous fat .…”
Section: Biological Actions Of Omega-3-derived Lipid Mediators In Watmentioning
confidence: 99%
“…Furthermore, both resolvin D1 (RvD1) and RvD2 have been shown to promote adiponectin secretion from adipose tissue explants ex vivo [62]. Neuhofer et al [63] also reported that obesity is associated with impaired local production of PD1 and 17-HDHA in fat, whereas treatment with 17-HDHA reduced adipose tissue inflammation and improved insulin sensitivity, which was associated with increased PPARγ expression and adiponectin levels in these animals. It is believed that the ability of PD1 and 17-HDHA to activate PPARγ and raise circulating adiponectin levels likely contributes to both antiinflammatory and insulin sensitizing effects of these DHAderived resolution mediators.…”
Section: Inflammation and Skeletal Muscle Insulin Resistancementioning
confidence: 94%